Meningeal rheumatoid nodules in a 55-year-old man presenting with chronic headaches and oculomotor nerve palsy: an uncommon extra-articular manifestation of rheumatoid arthritis. Issue 12 (9th December 2019) - Abdullah, Hafez Mohammad Ammar; Omar, Muhammad; Jbeli, Aiham; Fanciullo, Joseph
Abstract : Rheumatoid arthritis (RA) is a multisystem inflammatory disease which can involve many organ systems including the central nervous system (CNS). Though not very common, the results can be severely debilitating. The spectrum of the CNS involvement includes meningitis, encephalitis and occasionally rheumatoid nodules. Its presentation is variable, though very rarely it can present as focal neurological deficits. Imaging can be suggestive, but diagnosis usually requires tissue biopsy. Treatment consists of high-dose steroids and immunosuppressants. We describe the case of a 55-year-old male patient with a history of RA presenting with a third nerve palsy and headache who was found to have rheumatoid nodules on biopsy. CNS involvement in RA should be considered in anyone with rheumatoid arthritis who presents with focal neurological deficits, though infections and space-occupying lesions should also be ruled out.